Subjective Well-Being of a wife who is in a long-distance marriage - Dana, Adinda Rahma; Afdal, Afdal (Counseling and Humanities Review, 2022)
Marriages that occur between husband and wife who do not live together or live in two different areas are called long distance marriages. Long-distance marriage relationships require trust and confidence in the partner so as not to cause conflict in the marriage. The initial phenomenon in the field is that there are wives who have low subjective well-being when undergoing long distance marriages. The aim of this research is to describe the subjective well-being of wives who undergo long-distance marriages on the cognitive and affective aspects. This research uses a quantitative approach with a descriptive research type. The population in this study were wives who underwent long distance marriages in Sasak Ranah Pasisie District with a sample of 72 people, who were selected by total sampling technique. Collecting data in this study using a questionnaire using a Likert scale model. The results of this study revealed that in general, the subjective well-being of wives undergoing long-distance marriages in Sasak Ranah Pasisie District was in the moderate category with a percentage of 52.8%. Based on the subjective well-being aspect, it is categorized: (1) the cognitive aspect is in the high category with a percentage of 56.9%, (2) the affective aspect is in the medium category with a percentage of 44.4%. So it can be interpreted that wives who undergo long distance marriages have quite good subjective well-being. The results of this study can be used as input for counselors to provide premarital counseling and family counseling, and are expected to be able to provide counseling services to clients undergoing long distance marriage who have problems related to low subjective well-being through individual counseling and information services.